Competing ideologies in Greek culture, ancient and modern - Håland, Evy Johanne (Cambridge Scholars Publishing, 2019)
By using both modern and ancient sources, this volume explores the relationship between official religion and popular belief in Greece, as illustrated by the relations between competing ideologies, or the relationship between ideology and mentality. It shows that the communicative aspect of the religious festival is central, and allows the reader to get to know other sides of Greece than the picture that today dominates the news resulting from the economic crisis with which the county has struggled for several years.